(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Fish consumption is growing worldwide due to increased demand for healthier foods and advancements in processing. The fishing industry is a major source of revenue and employment, but various processing activities expose workers to diverse health problems. The study intended to assess health problems and safety practice among fish processing workers. Methods: This cross-sectional study was conducted on 335 fish processing workers from January 1 to December 31, 2021, using a multistage sampling method. Participants, aged 19 years and above, included both males and females, and the industries were selected purposively in the Chittagong district, a major coastal city in southeastern Bangladesh with a high concentration of fish processing industries. Data were collected through a semi-structured questionnaire and analysed descriptively. Results: The mean age of participants was 31.19±10.03 years, with the majority (34.6%) aged 20-29 years. Females made up 52.2% of respondents, and 43% had secondary-level education or higher. Musculoskeletal disorders were the most prevalent health problem (65.4%), followed by respiratory (38.5%), gastrointestinal (36.4%), eye (23.6%), and skin problems (20.6%), along with accidental injuries (6.6%). PPE use was inconsistent: 96.1% wore gloves, 93.4% wore rubber boots, 81.8% used masks, 6.3% wore goggles, and 3.3% used earplugs. Significant relationships (p≤0.05) were observed between health issues and age, gender, marital status, education, work experience, job section, overtime, and weekly working hours. Respiratory and eye problems were significantly associated with mask use. Conclusion: Fish processing workers are susceptible to various health problems, often due to improper PPE use. To address these issues, strategies must be developed to ensure consistent use of protective equipment and promote safer work practices, thereby improving worker health and well-being. JOPSOM 2024; 43(1): 41-45